2017
DOI: 10.1080/10350330.2017.1345111
|View full text |Cite
|
Sign up to set email alerts
|

“Our biggest killer”: multimodal discourse representations of dementia in the British press

Abstract: A recent (2016) Office for National Statistics report stated that dementia is now 'the leading cause of death' in England and Wales. Ever fixated with the syndrome (an unfailingly newsworthy topic), the British press was quick to respond to the bulletin, consistently headlining that dementia was the nation's 'biggest killer', while (re)formulating other aspects of the report in distorting and emotive metaphorical terms. In this paper we examine how the media, through use of a recurring set of linguistic and vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(53 citation statements)
references
References 50 publications
4
48
0
1
Order By: Relevance
“…The negative impact that misleading information regarding dementia portrayed by the media may have on people's adherence to healthier lifestyles for dementia risk reduction was strongly identified in our survey (Sub-theme 8). This corroborates findings from previous analyses of the UK media representations of dementia [23,26] which found that negative messages around dementia may lead to stigmatisation and misinformation and to the promotion of a dichotomy representing dementia in terms of "killer" and "victim". Our work extends the study by Peel [27] who defined such messages as "panic-blame", which may lead to individual culpability, similar to what we found in our survey.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The negative impact that misleading information regarding dementia portrayed by the media may have on people's adherence to healthier lifestyles for dementia risk reduction was strongly identified in our survey (Sub-theme 8). This corroborates findings from previous analyses of the UK media representations of dementia [23,26] which found that negative messages around dementia may lead to stigmatisation and misinformation and to the promotion of a dichotomy representing dementia in terms of "killer" and "victim". Our work extends the study by Peel [27] who defined such messages as "panic-blame", which may lead to individual culpability, similar to what we found in our survey.…”
Section: Discussionsupporting
confidence: 90%
“…A recent national survey conducted in the USA on individual perceptions of health conditions [21], in a sample of 4,033 respondents, found that cancer ranked as the most feared condition (40.3%) compared to dementia (17.5%). However, recent changes in the leading cause of death stating that dementia has overtaken cancer and cardiovascular disease, may change these perceptions in the future [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…Analysis methods included quantitative coding of how dementia was depicted, used more commonly with news media [40,60,66,67,70], framing analysis [26,32,63,69,76], discourse analysis [71], and Foucauldian analysis [75]. Quantitative studies were more likely to describe their methods, whereas papers from arts and media disciplines were less likely to explicitly describe methodology.…”
Section: Characteristics Of Included Papersmentioning
confidence: 99%
“…Papers showed that Alzheimer's was the most commonly depicted type of dementia [27,34], and the media often used the terms dementia and Alzheimer's interchangeably or together ( [26,64], Brookes et al 2018).…”
Section: Dementia Is Often Equated With Alzheimer's Diseasementioning
confidence: 99%
“…They argue that AD is continuing with this form of ageism through the targeted media focus on scary stories resulting in the public overestimating how common it is among older adults and in overdiagnoses by clinicians. The intensely lurid media representation not only fails to address the ageist misinformation surrounding dementia reporting, but it also likely aggravates the stress and depression frequently experienced by people living with dementia and their caregivers [13]. The only outcomes are fear and anxiety, further fuelling the frantic search to find a cure.…”
mentioning
confidence: 99%